Strategi Manajemen Rumah Tangga Melalui Pemanfaatan dan Inovasi Pupuk Komersial di Desa Ulak Kembahang II - Harunnurasyid Harunnurasyid; Suhel Suhel; Muhammad Subardin; shelly Febriana Kartasari; Mardalena Mardalena; Rahma Nida (UNIB Press, 2023)
The decreased level of income due to the Covid-19 pandemic is a challenge for the village government in achieving the welfare of its people. Expenditure levels have increased, and rural communities have difficulty meeting their basic needs. The problems that occur in Ulak Kembahang II Village are the lack of understanding, skill, and community creativity in managing the household economy. Therefore, the community service team carries out activities to manage the household economy of the village community by converting household waste into liquid organic fertilizer that can be used for personal consumption or sold. The dedication method was carried out by providing training and mentoring to participants who were attended by 29 housewives in Ulak Kembahang II Village. Based on the results of the evaluation, the average level of understanding of the material by the participants was 87.7% regarding the management of the household economy and the manufacture of liquid organic fertilizer. The people of Ulak Kembahang II Village can be more creative in managing household waste as an opportunity to increase income.